Family Reorganization in the Japanese Family Conciliation System: Resolving Divorce Disputes Involving Minor Children. (27th December 2018) - Harada, Ayako
Abstract: This article analyses the effectiveness of the Japanese court-annexed family conciliation mechanism in resolving divorce disputes involving conflicts pertaining to minor children, particularly child visitation, and discusses potential future directions for the family law system. Japanese family conciliation deals with many family disputes, including divorce disputes involving children. Although family courts have recently begun promoting more visitation agreements than in the past, they continue to face difficulties in facilitating workable agreements for families. An interview-based research project conducted by the author involving active conciliators revealed the unique strengths of conciliators' efforts in supporting the involved parties, as well as the systemic limitations of family conciliations in effectively navigating parties undergoing family transition. The research found that such limitations are related to the lack of clear legal rules as a guiding norm for negotiations between divorcing parents. This finding leads to the question of how we should develop legal norms for visitation and post-divorce family relationships. The author draws two possible scenarios and argues that both raise difficult questions that should be answered using knowledge acquired from social science research about the reality of current family relationships and the daily functioning of family law systems, including family conciliation.